Article RETRACTED due to manipulation by the authors The Effect Salvia Hispanica L Seed Extract on Blood Sugar Levels in Rats with Moderate Physical Activity - Reza Adityas Trisnadi; Rachmah Laksmi Ambardini; BM. Wara Kushartanti; Deni Hardianto; Panggung Sutapa; Karakauki Manil; Amran Amran; Rizqie Auliana; Danarstuti Utami; Desy Yunita Utami; Ardi Riyana; Ari Tri Astuti; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Hyperglycemia is a condition in which the body experiences an increase in the level of sugar in the blood and is a clinical manifestation of diabetes type. This unusual exercise can cause insulin resistance in patients with diabetes. Chia seeds contain a lot of antioxidants, which makes them effective in reducing oxidative stress caused by hyperglycemia and type 2 diabetes. The purpose of this study is to show the difference in the effect of the extraction of chia seeds and moderate exercise high blood sugar in T2DM. limit. and STZ injection. This research method is experimental and post-test control group design only. The number of samples is 15 male wistar rats aged 3-4 months with a weight of 180-200 grams repeated for 7 days, divided into 3 groups at random, that is the treatment group P0 as control, P1 received injection which. STZ and moderate exercise. and chia seed extract dose of 4.5 mg/kg body weight, P2 for STZ injection, for moderate exercise and chia seed extract dose of 13.5 mg/kg body weight/day. The duration of treatment is 7 days. Blood samples are taken from v. Ophthalmica on day 14. Monitor GDS level by spectrophotometer method. The data were analyzed by Anova test. The results of the study showed that the average blood sugar at P0: 128 ± 2.5; P1: 206±3.5; P2: 43.8±1.9. The results of the ANOVA test obtained a P value of 0.000 and the results of the LSD post hoc test between groups obtained a P value of 0.000 (<0.05). The conclusion of the study is that there is an effect of giving chia seed extract doses of 4.5mg/kgBW and 13.5mg/KgBW and moderate exercise can reduce blood sugar in time.